Speaking the unspeakable : religion, misogyny, and the uncanny mother in Freud's cultural texts - Jonte-Pace, Diane E. (Diane Elizabeth), 1951- (University of California Press, 2001)
In this bold rereading of Freud's cultural texts, Diane Jonte-Pace uncovers an undeveloped 'counterthesis, ' one that repeatedly interrupts or subverts his well-known Oedipal masterplot.